Effect of Electroacupuncture Combined with Traditional Chinese Medicine Fumigation and Traditional Exercises in Treating Knee Osteoarthritis Rehabilitation - Fangzhou TENG; Yaju ZHU; Tangyan CAI; Lulu HUANG; Jiemei GUO; Youxin SU (康复学报)
Objective:To observe the rehabilitation effect of electroacupuncture combined with traditional Chinese medicine fumigation and traditional exercises in knee osteoarthritis (KOA) treatment.Methods:A total of 78 KOA patients were randomly assigned to trial group and control group, with 39 cases in each group. All patients were given basic treatment, including health education and meloxicam. Traditional Chinese medicine fumigation and traditional exercises were given to the patients in the control group; the trial group was received electroacupuncture as an additional therapy on the basis of the control group treatment. The hierarchical quantitative score of KOA, the visual analogue scale (VAS) score, the dosage of meloxicam, five-times-sit-to-stand test (FTSST) and knee joint flexion and extension of two groups were evalued and analyzed after four weeks of treatment.Results:After the treatment, the hierarchical quantitative score of KOA, VAS score, and FTSST were lower than before, and knee joint flexion and extension of both groups were improved (P<0.01), the value differences before and after treatment of two groups had statistical significance (P<0.01).The dosage of meloxicam of the trial group was significantly less than the control group (P<0.01).Conclusion:Electroacupuncture combined with traditional Chinese medicine fumigation and traditional exercises could significantly relieve the pain, improve the comprehensive functions of knee joint and muscle strength of the lower limb, and increase the range of motion.